2020
DOI: 10.1097/scs.0000000000006673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zigzag Palatoplasty on the Repair of Cleft Palate and its Comparative Study With Sommerlad Palatoplasty and the Double Opposing Z Palatoplasty

Abstract: Purpose: At present, there are a variety of surgical methods for cleft palate repair, the authors first created the zigzag plasty of nasal mucosa musculature. The method is characteristic of better repair effect for anatomy and function of palatopharyngeal compared with the traditional method. Methods: Fifty patients with cleft palate were involved in this study, and treated with 3 different operative methods, respectively: zigzag palatoplasty for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Nevertheless, Furlow palatoplasty not only restored the velar muscular sling to proper orientation but also elongated the velar length reducing the risk of longitudinal scar contracture. Consequently, the Furlow repair has a stronger ability to extend the soft palate length than sommerlad palatoplasty (18). After 289 patients with cleft palate repaired by Furlow palatoplasty, Chorney et al (27) found only 5% of the patients needed secondary surgery as a result of VPI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, Furlow palatoplasty not only restored the velar muscular sling to proper orientation but also elongated the velar length reducing the risk of longitudinal scar contracture. Consequently, the Furlow repair has a stronger ability to extend the soft palate length than sommerlad palatoplasty (18). After 289 patients with cleft palate repaired by Furlow palatoplasty, Chorney et al (27) found only 5% of the patients needed secondary surgery as a result of VPI.…”
Section: Discussionmentioning
confidence: 99%
“…The former was by means of dissection and reposition of the levator veli palatini, while the latter was achieved with the help of the double-opposing Z-plasty. Previously, several studies had evaluated the clinical outcomes of these two surgical procedures (16)(17)(18)(19)(20). Khosla et al reported Furlow Z-plasty yielded excellent speech results for primary cleft palate repair, and the rate of VPC reached 84% (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al . [ 25 ] introduced a new modification to lengthen the soft palate by making a multiple zigzag incision in the nasal mucosa which is named zigzag plasty. Their study showed a good lengthening of the soft palate than compared to other methods.…”
Section: Discussionmentioning
confidence: 99%